Causal effects of subsidized career breaks - Oskar Nordström Skans; Linus Lindqvist (Institute for Labour Market Policy Evaluation (IFAU), 2005)
The paper uses a quasi-experimental situation to analyze the effects of career interruptions on future labor market outcomes. Data are generated by a Swedish program that granted career breaks to applicants until funds where exhausted. Comparing approved and declined (due to lack of funds) applications allows us to derive “pure” effects of interrupted career that are not confounded by selection or omitted variables. The results show no significant effects on working hours but give some support for increased retirement probabilities among the oldest workers. The average wage effect is negative and in the order of 3 percent 1–2 years after the break. Further evidence suggests that one reason for the large negative wage effects may be related to changes in jobs and tasks.
Keywords: J22; J24; J26; J31; 330; Career interruptions; labor supply; wages; natural experiment; Erwerbsverlauf; Arbeitszeitgestaltung; Arbeitsangebot; Test; Prognose; Theorie; Schweden